The Students’ Self-Confidence in Public Speaking - Arina; Ikhrom; Nadiah Nadiah (ELITE JOURNAL, 2019)
This study aims to describe and analyze the students’ self-confidence in public speaking at Advanced Speaking Class of English Education Department at Walisongo State Islamic University in the Academic year of 2018/2019. This study deals with Lauster theory, that tells about self-confidence is convincing in the ability and self-assessment of the task and it has an effective approach. This study applied a descriptive qualitative method. The data were collected through a questionnaire with 15 questions for 30 students, observation of the students’ performance in public speaking with 10 checklists and interview with 6 students in order to gain the students’ self-confidence. The technique of data analysis involved data reduction, data display, and conclusion drawing/verification by using Creswell. The result shows that the students’ confidence level at an advanced speaking class was at the adequate level. From the result of a questionnaire, it shows that the mean score of students’ self-confidence was 3,2 while from the result of observation, it shows that students did several lacks of performances, such as no eye contact, speaking with vibration, making repetition, giving many movements, and also giving many pauses. The influencing factors which lead to students’ self-confidence were such as having a negative mindset, lack of motivation, lack of practice, lack of vocabulary, lack of ability, and lack of preparation.